Islamic Corporate Social Responsibility Effect on Financial Performance and Reputation In OJK-Listed Banks - Rizwanti, Jihan Dwi; Maknuun, Lu’lu’ Il; Yusri Aftian, Rahman (Invest Journal of Sharia & Economic Law, 2023)
This study investigates the impact of Islamic Corporate Social Responsibility (ICSR) on financial performance and corporate reputation in the context of Islamic commercial banks in Indonesia. Specifically, it examines how ICSR affects return on assets (ROA) and return on equity (ROE) as indicators of financial performance and deposits from customers (DPK) as a measure of firm reputation. The research uses data from the annual reports of nine Shariah commercial banks over five years, from 2015 to 2019.  The results show that ICSR does not significantly affect ROA, indicating a limited impact on banks' asset-based financial performance. However, ICSR has a positive effect on ROE, suggesting that it enhances investor confidence and contributes positively to equity-based financial performance. In contrast, the study concludes that ICSR does not have a significant impact on corporate reputation, suggesting the complexity of factors that influence public perception beyond ICSR activities. This research provides valuable insights into the differential impact of ICSR on different dimensions of Islamic commercial banks' performance and highlights potential areas for further research in the field of corporate social responsibility and financial management in the Islamic banking sector.